Work-Related Musculoskeletal Diseases and the Workers' Compensation - Jang, Tae-Won (The Korean Academy of Medical Sciences, 2014)
The Industrial Accident Compensation Insurance Act (IACIA) regulates the workers' compensation insurance system and the standards for the recognition of occupational diseases (ODs). Since its establishment in 1994, the IACIA has been amended several times. Before 2008, the approval of compensation for work-related musculoskeletal diseases (WMSDs) was decided based on the recommendation of consultants of the Korea Workers' Compensation and Welfare Service (COMWEL). The IACIA was amended in 2008, and since then, the approval of compensation for occupational injuries has been decided based on the recommendation of COMWEL consultants, whereas the approval of compensation for ODs was decided based on the judgment of Committee on Occupational Diseases Judgment (CODJ) which was established in 2008. According to the 2013 amendment to the IACIA, degenerative musculoskeletal diseases among workers engaged in musculoskeletal-burdening work should be considered compensable ODs. Despite some commendable changes to the workers' compensation insurance system, other significant issues persist. To resolve these issues, related organizations including the associations of orthopedic surgery, neurosurgery, and occupational and environmental medicine; Ministry of Employment and Labor; and COMWEL need to work cooperatively. GRAPHICAL ABSTRACT: [Image: see text]